A Study on Milk Yield, Fertility and Milk Quality Characteristics of Primiparous Red-Holstein and Holstein-Friesian Cows - Atakan Koç; Ramazan Gürses (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the reproductive characteristics, milk yield and milk quality of Primiparous Red-Holstein (RH) and Holstein-Friesian (HF) cows. For this aim, records and monthly taken milk samples of 83 RH and 14 HF raised on a farm in Aydın, Turkey were used. The averages of the first calving age (FCA), gestation length (GL), days open (DO), calving interval (CI), daily milk yield (DMY), 305-day milk yield (305-dMY), solid non-fat (SNF) and Log10 somatic cell count (Log10SCC) of milk were found to be 27.6±0.24 mo, 278.4±1.09 d, 144.0±7.12 d, 421.4±7.66 d, 22.7±0.21 kg, 6981±137.0 kg, 9.8±0.04% and 4.59±0.024 (38905 cells/ml), respectively. Except for DMY, the differences between the breeds were statistically insignificant for FCA, GL, DO, CI, 305-dMY, SNF and Log10SCC. DMY averages for RH and HF were 21.8±0.21 kg and 24.3±0.49 kg, respectively. The effect of season on FCA and the effect of lactation month on SNF and Log10SCC were also found to be statistically significant. Apart from DMY, not any significant difference was observed between RH and HF breeds in terms of the characteristics emphasized.